Loxapine for Treatment of Patients With Refractory, Chemotherapy-Induced Neuropathic Pain: A Prematurely Terminated Pilot Study Showing Efficacy But Limited Tolerability - Schmiedl, Sven; Peters, David; Schmalz, Oliver; Mielke, Anke; Rossmanith, Tanja; Diop, Shirin; Piefke, Martina; Thürmann, Petra; Schmidtko, Achim (Frontiers in Pharmacology, 2019)
Neuropathic pain is a debilitating and commonly treatment-refractory condition requiring novel therapeutic options. Accumulating preclinical studies indicate that the potassium channel Slack (KNa1.1) contributes to the processing of neuropathic pain, and that Slack activators, when injected into mice, ameliorate pain-related hypersensitivity. However, whether Slack activation might reduce neuropathic pain in humans remains elusive. Here, we evaluated the tolerability and analgesic efficacy of loxapine, a first-generation antipsychotic drug and Slack activator, in neuropathic pain patients. We aimed to treat 12 patients with chronic chemotherapy-induced, treatment-refractory neuropathic pain (pain severity ≥ 4 units on a 11-point numerical rating scale) in a monocentric, open label, proof-of-principle study. Patients received loxapine orally as add-on analgesic in a dose-escalating manner (4 treatment episodes à 14 days, daily dose: 20, 30, 40, or 60 mg loxapine) depending on tolerability and analgesic efficacy. Patient-reported outcomes of pain intensity and/or relief were recorded daily. After enrolling four patients, this study was prematurely terminated due to adverse events typically occurring with first-generation antipsychotic drugs which were reported by all patients. In two patients receiving loxapine for at least two treatment episodes, a clinically relevant analgesic effect was found at a daily dose of 20-30 mg loxapine. Another two patients tolerated loxapine only for a few days. Together, our data further support the hypothesis that Slack activation might be a novel strategy for neuropathic pain therapy. However, loxapine is no valid treatment option for painful polyneuropathy due to profound dopamine and histamine receptor-related side effects. (EudraCT Number: 2014-005440-17 (https://www.clinicaltrialsregister.eu), NCT02820519 (https://clinicaltrials.gov/))